The kinesthetic differentiation ability of table tennis players - Bankosz, Z. (Human Movement, 2012)
The aim of this study was to evaluate the differences between two groups of table tennis players (differing by their level of play) in terms of the kinesthetic differentiation ability of their so-called spatial component. Methods. The study was conducted using a goniometer which assessed the accuracy of performing an arm movement, specifically, the pronation and supination of the forearm at the elbow. The study analyzed the accuracy rate of performing this movement, where a smaller value indicated a higher level of kinesthetic differentiation ability. Results. In all four tasks, the more advanced (skill-wise) group of players obtained lower arithmetic mean and median values of accuracy than the group that played at a lower skill set. This may suggest the importance of the tested variable as an important component of table tennis. However, the tested groups did not significantly differ from each other in the accuracy of performing the studied movement. Nonetheless, the variability of the accuracy rate of the lower skill level group was considerably larger than the more advanced and skilled group. Conclusions. It can be assumed that the more advanced group is more homogeneous in terms of accuracy production. This could be the result of specific training exercises.